APPLYING THE GOOGLE EARTH ENGINE CLOUD COMPUTING PLATFORM IN ENVIRONMENTAL RESEARCH: FORECASTING FUTURE LAND USE AND LAND COVER MAP - Yen Hai Hoang, Dong Phuong Nguyen, Hoa Thi Nguyen, Quoc Phi Nguyen, Ngoc Thi Tran (Chelonian Research Foundation, 2024)
Hanoi City is Vietnam's cultural, political, and economic centre, where dense population and rapid urbanisation pose many challenges to planning effective land use and sustainability. The study used a real-time satellite image data set for land cover classification Dynamic World V1 data to analyse land cover changes for Hanoi city from 2018 to 2022 combined with high-resolution digital elevation data and using random forest algorithms to predict future land cover classification. The results show a significant increase in Crops and Built areas in the future and a substantial decrease in the city's agricultural land, trees, and bare land. The model has a reasonably high classification accuracy of about 74.2% and a Kappa coefficient of 0.6688. The research results have also shown the ability to apply cloud computing on the Google Earth Engine tool platform to forecast land use cover changes. This is a scientific basis that provides information to help managers come up with long-term strategies for sustainable urban development.